Anxiety, Depression, and Their Related Factors Among Parents/Guardians of Students Affected by Nigerian University Staff Strikes - Patrick Ayi Ewah; Idoo Womboh; Peter Agba Awhen; Felicia Agbor-Obun Dan (علوم بهداشتی ایران)
Background and Purpose: In literature, the psychological states of students’ parents/guardians have been neglected when assessing the negative effects of university strikes. This study aims to determine the anxiety and depression among parents/guardians of students during the university staff strike in Nigeria and identify the determinant factors and predictors. Materials and Methods: This cross-sectional study was conducted on 214 healthy adults (parent/guardians of students) aged 22-73 years during the university staff strike in 2022 in Nigeria. Their psychological states, and socio-demographic/economic characteristics were evaluated using a structured questionnaire, the general anxiety disorder 7-item scale, and the patient health questionnaire 2-item. Data were analyzed using descriptive statistics, logistic regression analysis, and the Pearson correlation test. The significant level was set at 0.05. Results: Most of the participants were in mid-late adulthood (78%) and female (57%). The prevalence of anxiety and depression was 62.1% and 27.6%, respectively. Gender (P=0.052), level of education (P=0.001), frequency of leaving home per week (P=0.048), and number of children in the university (P=0.001) were significantly associated with anxiety. Depression was significantly associated with the level of education (P=0.019), steady family income (P=0.016), and type of exercise (P=0.059). The level of education (OR=4.185, 95% CI, 1.531%, 11.436%, P=0.005) and number of children in the university (OR=0.340, 95% CI, 0.157%, 0.735%, P=0.006) could significantly predict anxiety, while knowing a worker/student who died during the strike (OR=2.018, 95% CI, 1.01%, 4.033%, P=0.047) predicted depression. Conclusion: The university staff strikes in Nigeria pose a major threat to the psychological health of students’ parents/guardians. A high level of education, male gender, less frequency of leaving home, and more number of children in the university are related to increased anxiety in parents/guardians. Also, a low level of education, a steady family income and engagement in aerobic exercise are related to decreased depression. We recommend parents to regularly engage in aerobic exercise, and jobs should be provided to them during strikes to boost their family income.